Applejack and the honest-to-goodness switcheroo - Berrow, G. M. (New York ; Boston : Little, Brown and Company, 2014)
"Applejack starts a diary to record all her hard work bucking fields at Sweet Apple Acres. As the days pass, Applejack's journal entries start to read like lists of complaints as she writes honestly about whatever is bothering her. But when the book falls into the wrong hooves, Applejack finds herself in a real pickle!"--
Keywords: JUVENILE FICTION / Humorous Stories; JUVENILE FICTION / Media Tie-In.; JUVENILE FICTION / Fantasy & Magic